2016
DOI: 10.1039/c6sc03239g
|View full text |Cite
|
Sign up to set email alerts
|

Photothermal-enhanced catalysis in core–shell plasmonic hierarchical Cu7S4microsphere@zeolitic imidazole framework-8

Abstract: A strategy to improve reaction activity via the photothermal effect of plasmonic semiconductor nanomaterials is demonstrated in a core–shell structured catalyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
79
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 104 publications
(84 citation statements)
references
References 50 publications
(33 reference statements)
4
79
0
1
Order By: Relevance
“…Under UV light irradiation, photothermal catalysis was not obviously enhanced, which implies that there is a conflict between the photogenerated charges and photothermal conversion. Xu et al [120] focused on the highly efficient photothermal conversion based on plasmons. The better photothermal conversion properties led to a more efficient photothermal catalyst for CO 2 reduction with H 2 .…”
Section: Photothermal Catalysismentioning
confidence: 99%
“…Under UV light irradiation, photothermal catalysis was not obviously enhanced, which implies that there is a conflict between the photogenerated charges and photothermal conversion. Xu et al [120] focused on the highly efficient photothermal conversion based on plasmons. The better photothermal conversion properties led to a more efficient photothermal catalyst for CO 2 reduction with H 2 .…”
Section: Photothermal Catalysismentioning
confidence: 99%
“…It is demonstrated that the photothermal effect played a positive role for the Pdcatalyzed organic hydrogena tion reaction and the hotelectron effect played a negative role, which coincided with the ultrafast absorption spectros copy characterizations for different plasmonic modes of Au nanorods. Along with previous works, [33,88,90] the feasibility of photothermal catalysis has been verified to maximize the catalytic activity by delicate materials design, which should be exerted appropriately into the establishment of efficient solar energy conversion system. From another openminded viewpoint, this strategy provides an alternative way to realize the conventional thermal catalysis in the photothermal path way, e.g., photothermal CO 2 hydrogenation, methane activa tion, water-gas shift reaction, Fischer-Tropsch synthesis, etc.…”
Section: Discussionmentioning
confidence: 99%
“…They proposed a mecha nism that the hot holes generated by the plasmonic Cu 7 S 4 nanocrystals injected into the Pd nanoparticles and rendered these reactions being occurred. In the recent work by Xu and coworkers, [88] the photothermalenhanced catalysis was achieved in the core-shell plasmonic hierarchical Cu 7 S 4 micro sphere@ZIF8 (Cu 7 S 4 @ZIF8) structures (Figure 11a-d). The laser experiments showed that the plasmoninduced photo thermal effect is responsible for the improved catalytic activity.…”
Section: Organic Photosynthesis and Other Photocatalytic Reactionsmentioning
confidence: 99%
“…This can be avoided by the encapsulationo fP dN Cs inside porousm aterials as shells with small pore openings, which also enable the size-selective hydrogenation of different substrates. [74] Wang et al [76] reported ac ore-shell Cu 7 S 4 @ZIF-8n anostructure and demonstrated that the core and shell sections of the composite were endued with thermo-and photocatalytic functionality,r espectively.T he hierarchicalC u 7 S 4 hollow microsphere core acts as ap lasmonic nanoheater with at hermophotocatalytic transductione fficiency of 31.1 %a nd the surface temperature increasedt o9 4 8Cu nder the irradiation of a 1450 nm laser.T he localized heat converted from light energy Figure 12. In ar ecent work, ar epresentative MOF,{ Zn(2-methylimidazole) 2 }( ZIF-8), was grown on Pd NCs to obtain Pd NCs@ZIF-8 with ac ore-shell structure ( Figure 12).…”
Section: Value-added Organic Compoundsmentioning
confidence: 99%